1995
DOI: 10.1183/09031936.95.08101669
|View full text |Cite
|
Sign up to set email alerts
|

Use of pulse transit time as a measure of inspiratory effort in patients with obstructive sleep apnoea

Abstract: U Us se e o of f p pu ul ls se e t tr ra an ns si it t t ti im me e a as s a a m me ea as su ur re e o of f i in ns sp pi ir ra at to or ry y e ef ff fo or rt t i in n p pa at ti ie en nt ts s w wi it th h o ob bs st tr ru uc ct ti iv ve e s sl le ee ep p a ap pn no oe ea a ABSTRACT: Pulse transit time (PTT) is the time taken for the arterial pulse pressure wave to travel from the aortic valve to a peripheral site. For convenience, it is usually measured from the R wave on the electrocardiogram to the pulse wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(110 citation statements)
references
References 10 publications
(11 reference statements)
3
103
1
3
Order By: Relevance
“…Regardless of this, PTT has become an increasingly popular noninvasive measure of abrupt changes in arterial stiffness or fluid properties of blood. 11,12 In this study, a trough in arterial distensibility was unable to be located at the age of 10 years as reported. 7 This is perhaps expected as progressive medial degeneration is probably the major underlying factor; however, this needs further clarification.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…Regardless of this, PTT has become an increasingly popular noninvasive measure of abrupt changes in arterial stiffness or fluid properties of blood. 11,12 In this study, a trough in arterial distensibility was unable to be located at the age of 10 years as reported. 7 This is perhaps expected as progressive medial degeneration is probably the major underlying factor; however, this needs further clarification.…”
Section: Discussionmentioning
confidence: 40%
“…8 The greater PTT value at the toes can be easily explained by its relatively longer artery length the pulse wave needs to propagate. 11,12 HR effects on PWV was often dismissed or even overlooked; however, recent studies have suggested otherwise. Studies conducted on animals have established that arterial distensibility is a function of HR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works have suggested that there could be other markers of arousal which are much easier to measure than EEG and which could assess the true extent of sleep fragmentation. This is the case for the pulse transit time, a non-invasive measure of blood pressure, a semiquantitative measure of respiratory effort [25][26][27] and a sensitive marker of autonomic arousals [20]. The recently developed peripheral arterial tonometry, based on detection of peripheral vasoconstriction, has been shown to be a sensitive marker of sympathetic arousal [28] and apneas [9,29].…”
Section: Discussionmentioning
confidence: 99%
“…The pulse transit time provided information on inspiratory effort [20] and autonomic arousals [19,21]. All studies were analysed by standard procedures used in the authors' unit.…”
Section: Diagnostic Sleep Studiesmentioning
confidence: 99%